Evaluasi Pengelolan Persampahan Di Kota Enrekan Kabupeten Enrekang - Rezky Rifaldi; Syafri Syafri; Ilham Yahya (Journal of Urban Planning Studies, 2021)
The purpose of this study was to determine and evaluate solid waste management in Enrekang City, Enrekang Regency. The variables used consisted of 5 including: (X1) storage; (X2) Collection; (X3) Transportation; (X4) Final Disposal; (Y) Operational Engineering. The analytical method used is in the form of descriptive analysis, by describing or describing clearly the conditions that occur in the research location based on the provisions of existing waste management techniques. It is known that several variables are source of container, collection, transportation, and final disposal (TPA). Where from the results of the analysis obtained, there are several factors that influence the low level of solid waste management in Enrekang City from the operational aspect due to the condition of waste management in Enrekang City in terms of quality and quantity of infrastructure as well as inadequate aspects of non-infrastructure, this is due to the condition of the City area. Enrekang is quite large with mountainous geographical